The Production and Organoleptic Test of Onion Peel Eco enzyme - Adelina Maryanti; Fitri Wulandari (Jurnal Biologi Tropis, 2023)
Eco enzyme is a fermented organic waste liquid that can be used as a cleaning agent, natural fertilizer and effective pesticide. The organic waste, including vegetable residues and fruit pulp, can be processed into eco enzymes. Household activities are one source of organic waste by leftover cooking spices such as onion peels. Peoples don’t know the utilizing and treatment of organic waste such as onion peels. It has many usefullness. Onion peel is high in antioxidants and bioactive substances such as flavonoids and quarcetinwhich is very good for immune system maintenance. Furthermore, it contains allicin substances which have antimicrobial activity as antibacterial and antifungal agents. Onion peel can be used as a natural pesticide and fertilizer. Onion peels utilities can be processedby produceeco enzymes. This research aims to learn how to produce eco enzymes using onion peel as a source of household organic waste and how its organoleptic characteristics. The kind of study carried out is an investigation of the study's formulation are sugar: onion peel: water (1:3:10). The method used in this research is qualitative within the characteristic organoleptic test.The result of this research through mixing all the ingredients and three monts of fermentation to produce eco enzyme. The organoleptic characteristics of onion peel eco enzyme were sour of aroma, dark brown liquid and 98% of volume